The FDA-approved drug Auranofin has a dual inhibitory effect on SARS-CoV-2 entry and NF-κB signaling - Emmanuel Laplantine; Christine Chable-Bessia; Anne Oudin; Jitendryia Swain; Adèle Soria; Peggy Merida; Manon Gourdelier; Sarra Mestiri; Indira Besseghe; Erwan Bremaud; Aymeric Neyret; Sebastien Lyonnais; et al. (iScience, 2022)
Summary: Patients with severe COVID-19 show an altered immune response that fails to control the viral spread and suffer from exacerbated inflammatory response, which eventually can lead to death. A major challenge is to develop an effective treatment for COVID-19. NF-κB is a major player in innate immunity and inflammatory process. By a high-throughput screening approach, we identified FDA-approved compounds that inhibit the NF-κB pathway and thus dampen inflammation. Among these, we show that Auranofin prevents post-translational modifications of NF-κB effectors and their recruitment into activating complexes in response to SARS-CoV-2 infection or cytokine stimulation. In addition, we demonstrate that Auranofin counteracts several steps of SARS-CoV-2 infection. First, it inhibits a raft-dependent endocytic pathway involved in SARS-CoV-2 entry into host cells; Second, Auranofin alters the ACE2 mobility at the plasma membrane. Overall, Auranofin should prevent SARS-CoV-2 infection and inflammatory damages, offering new opportunities as a repurposable drug candidate to treat COVID-19.